EVALUASI KINERJA KEUANGAN PERUSAHAAN DAERAH PRODEXIM PALEMBANG - kusminaini armin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2012)
This study reviews the evaluation of financial management in particular financial management area Prodexim Palembang. The studies carried out in the Company's area of Palembang Prodexim as for the issue raised in this study is how the picture of the Company's financial performance Prodexim Palembang area from 2005 till the year 2009. The purpose of this study is to evaluate the financial performance measured by financial ratios (liquidity ratios, activity ratios, leverage ratios and profitability ratios). The data of this study uses quantitative and qualitative data. The instrument is used to analyze the company's financial statements, the financial ratio analysis techniques.The results of this study showed a rise and fall of the level of health Prodexim regional companies from 2005 till 2009, where in the last three years shows an increase in the liquidity ratio for the better, while the activity ratios, leverage and profitability ratios showed a decline of four years with less status.The conclusion of this study of the company's current ratio in 2007, 2008 and 2009 were good enough significant preusan ability to pay short-term debt is illiquid. Judging from the activity ratios, leverage and profitability ratios Raio is not good, it means the company is less efficient in managing their assets, companies are less able to meet the long-term debt as well as the company's ability to capitalize on low. Suggestions on research companies maintain corporate liquidity ratio, more efficiently manage its assets primarily current assets, debt collection should be optimized. Management should make greater efforts to increase its income.Ã‚Â Keywords: Corporate Financial Performance, financial ratio